Pengelompokan Mahasiswa Berdasarkan Capaian Pembelajaran Lulusan Menggunakan K-Means Clustering di Program Studi Teknik Informatika UNIKOM - Agustia, Richi Dwi; Finandhita, Alif (Komputa : Jurnal Ilmiah Komputer dan Informatika, 2025)
The Outcome-Based Education (OBE) curriculum emphasizes learning outcomes as benchmarks of graduate competence. This study in the Informatics Engineering Program at UNIKOM aims to cluster students based on the fulfillment of Learning Outcomes (CPL) to more accurately identify graduate professional tendencies. The dataset consists of 336 OBE cohort students, 58 core courses, and 312,793 academic records. The K-Means clustering method was applied with preprocessing steps including removal of missing values, duplicates, and non-relevant general courses (MKDU). Cluster validity was evaluated using the Davies–Bouldin Index (DBI) and Silhouette Score. The results yielded four clusters: (1) hardware integration and technology consultancy, (2) basic programming and data management, (3) systemic and managerial competence in information systems, and (4) data analytics, business intelligence, and predictive modeling. Evaluation metrics (DBI = 1.18; Silhouette Score = 0.27) indicate reasonably valid clustering despite intra-cluster variation. This study provides a strategic contribution to curriculum development in the Informatics Engineering Study Program at UNIKOM, particularly in aligning graduate profiles with the demands of the digital technology-driven workforce.